Keanekaragaman Tumbuhan Berkhasiat Obat di TWA Gunung Tampomas - Putra Restu Wicaksono (Wanamukti: Jurnal Penelitian Kehutanan, 2020)
Forests are biological natural resources that have provided development benefits in Indonesia during their specific “Orde Baru” government of the timber forest product sector, but the impact of high exploitation has had considerable damage. Therefore it is necessary to find alternative efforts in forest utilization. One such effort is to utilize plants that can be used as medicinal plants. Medicinal plants are an alternative use of forest products from the non-timber sector. One of the places that need to know the existence of medicinal plants is Taman Wisata Alam Gunung Tampomas. Lack of data from the types of medicinal plants in this area feared damaged and extinction.The results of this research found 21 species of medicinal plants consisting of 19  types of non-tree vegetation and 2 types of tree vegetation. Non-tree vegetation is dominated by the type of Eupatorium riparium with Relative Frequency of 8.60%. While the tree vegetation was dominated by Melia azedarach species with INP value in each strata of seedlings, piles, poles, and trees respectively 9.02%, 11.97%, 18.14% and 20.43%. Most of the medicinal plants have the benefit of fever, abdominal pain, urine, malaria, bleeding such as Imperata cyindrica, Melia azedarach, Ageratum conyzoides, Quassia amara, Angioptris evecta and Eupatorium ripariumBenefit from this research about existence of medicinal plants in the area of Blok Paseban and Blok Pasir Sabeulah TWA Gunung Tampomas, the community can make this area as a source of germplasm so that the existence of medicinal plants can be preserved sustainability. In addition, people around the area can cultivate medicinal plants outside the area of TWA Gunung Tampomas